2020
DOI: 10.1109/access.2020.3023961
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Incident Detection Method Based on Factor Analysis and Weighted Random Forest

Abstract: Timely and accurate detection of traffic incidents can effectively reduce personal casualties and property losses, and improve the ability of macro-control and scientific decisionmaking of traffic. The unbalance of traffic incident data has a great influence on the detection effect. Therefore, a traffic incident detection method based on factor analysis and weighted random forest (FA-WRF) is designed. Through the analysis of the change rule of traffic flow parameters to build the initial incident variable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Random forest (RF) was used to train the data set, and Matthews correlation coefficient (MCC) is calculated for the classification results as a new weight value to test data, so as to improve the overall classification performance of random forest algorithm for unbalanced data. The experimental results demonstrate that the model based on FA-WRF has better classification effect and is more competitive in dealing with imbalanced data classification [22]. In 2020, a hybrid AID method using Random Forest-Recursive Feature Elimination (RF-RFE) algorithm and Long-Short Term Memory (LSTM) network optimized by Bayesian Optimization Algorithm (BOA) was proposed.…”
Section: Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Random forest (RF) was used to train the data set, and Matthews correlation coefficient (MCC) is calculated for the classification results as a new weight value to test data, so as to improve the overall classification performance of random forest algorithm for unbalanced data. The experimental results demonstrate that the model based on FA-WRF has better classification effect and is more competitive in dealing with imbalanced data classification [22]. In 2020, a hybrid AID method using Random Forest-Recursive Feature Elimination (RF-RFE) algorithm and Long-Short Term Memory (LSTM) network optimized by Bayesian Optimization Algorithm (BOA) was proposed.…”
Section: Machine Learningmentioning
confidence: 99%
“…For Problem 1: for the scarcity of samples, there are three common strategies: 1) improve the algorithm itself to apply to the dataset [22], 2) cost-sensitive learning approaches, 3) change the size of the sample. In contrast, because the third strategy is more simple to use, the application scope is more widely and popular.…”
Section: Ensemble Learningmentioning
confidence: 99%
“…2 are the Lagrangian multipliers [31], ρ is the penalty coefficient ( > 0), and tr is the trace of the matrix, that is, the sum of the diagonal elements in the matrix. e iterative calculation formula of ( 9) is…”
Section: Optimization Solutionmentioning
confidence: 99%
“…In recent years, research on cold chain logistics distribution has concentrated on solving the VRP [10][11][12][13][14]. However, considering the spoilage of fresh food and the complex traffic environment, researchers found that the shortest paths may not necessarily lead to the lowest distribution cost.…”
Section: Introductionmentioning
confidence: 99%